Preparation of Mesoporous Carbon Nitride Photocatalyst with Tunable Band Structure by Copolycondensation of Dicyandiamide and Urea - Wan1, J.; Hu2, S.Z.; Li2, F.Y.; Fan2, Z.P.; Lu3, G.; Zhang4, J. (Asian Journal of Chemistry, 2014)
A convenient template free method to prepare mesoporous g-C3N4 with a tunable band structure was reported by copolycondensation of dicyandiamide and urea. X-ray diffraction, N2 adsorption, elemental analysis, UV-visible spectroscopy, photoluminescence and X-ray photoelectron spectroscopy were used to characterize the prepared catalysts. The results indicated that copolycondensation of dicyandiamide and urea strongly influenced the polycondensation degree of prepared mesoporous g-C3N4 materials, leading to the difference in structural property, optimal property and electronic structure. The activities of prepared catalysts were tested in the photocatalytic degradation of Rhodamine B under visible light. The mass fraction of urea plays the important role on the photocatalytic performance. The possible mechanism was proposed.